Домашнє навчання як альтернативна форма здобуття початкої освіти (за ідеями американського педагога Джона Холта) - Рубан, Лариса (Studies in Comparative Education, 2014)
Стаття розкриває зміст домашнього навчання, його переваги за певних обставин та поширення в країнах Європи за ідеями американського педагога Джона Холта. Інтерес світової педагогічної спільноти до спадщини Джона Холта викликаний, перш за все, тим, що ім’я педагога стало символом домашнього навчання. Спочатку ідеї Джона Холта поширювалися у англомовному світі, а у зв’язку зі стрімким ростом домашньої освіти набули транснаціонального освітнього характеру. Поширення ідей Джона Холта відбувається завдяки активній діяльності громадської освітньої організації – Асоціації Джона Холта. Статья раскрывает содержание домашнего обучения, его преимущества при определенных обстоятельствах и распространение в странах Европы по идеям американского педагога Джона Холта. Интерес мирового педагогического сообщества к наследию Джона Холта вызван, прежде всего, тем, что имя педагога стало символом домашнего обучения. Сначала идеи Джона Холта распространялись в англоязычном мире, а в связи со стремительным ростом домашнего образования приобрели транснациональный образовательный характер. Распространение идей Джона Холта происходит благодаря активной деятельности общественной образовательной организации – Ассоциации Джона Холта. The article reveals the contents of homeschooling, its benefits under certain circumstances and spreading throughout Europe by the ideas of American educator John Holt. The interest of the world pedagogical community to the inheritance of John Holt is caused of the fact that his name has become a symbol of homeschooling. John Holt’s ideas were spreading in the English-speaking world, but due to the rapid growth of homeschooling they have gained transnational educational character. In the world pedagogical community the ideas of John Holt are spread due to the activity of the public educational organization – Holt Associates. In the mid - 80s of the XX century the movement in support of homeschooling was primarily an American phenomenon, in Europe this form of education was considered illegal and strictly limited. Today, the largest European company in support of homeschooling is the UK, where in 2000 approximately 10,000 children were educated at home. The article provides information about homeschooling in Australia, Argentina, Austria, Belgium, Bulgaria, Greece, Denmark, Spain, Italy, Germany, Poland, Russia, Hungary, Finland and France. John Holt’s ideas are embodied in a number of papers which received spreading and usage in many countries. Data analysis of the existence of alternative form of education – homeschooling – indicates that in some countries homeschooling is widely implemented and confirmed by law. In the developed countries homeschooling is becoming more common and this fact requires improvement of pedagogical skills and the need of alternative forms of education.